Geographies of ethnic segregation in Stockholm: The role of mobility and co-presence in shaping the 'diverse' city. (September 2019) - Rokem, Jonathan; Vaughan, Laura
This article assesses how urban segregation and ethnic diversity in Stockholm have been shaped by spatial policy and migration trajectories over time. Much of the urban studies and planning literature defines segregation as a measure of residential mixing. In contrast, our research suggests that segregation could be understood as a lack of opportunities for interaction in public space. In the case of Stockholm, space syntax network analysis and the establishment of ethnicity as a statistical category suggest that despite the social infrastructure provided by the Swedish state, the city's specific spatial configuration alongside its policies of housing allocation have resulted in severe constraints on the potential for co-presence between new immigrants and the native Swedish population. Spatial analysis suggests that the city's public transport infrastructure is a contributory factor in maintaining separation between foreign-born and ethnic Swedes. Coupled with a high level of social deprivation amongst new immigrants, the result is a multi-dimensional spatial segregation process that persists amongst the second immigrant generation, reinforcing ethnic and socio-economic area-based housing segregation. We conclude that despite Sweden's long-standing political vision of social integration, its capital is suffering from increasing ethnic spatial differentiation, which will most likely persist unless a greater consideration of spatial connectivity and an introduction of ethnic and racial equality data in policy and practice are brought to bear.